2020
DOI: 10.2478/amns.2020.1.00029
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to (3+1) Dimensional Boiti–Leon–Manna–Pempinelli Equation

Abstract: In this article, some new travelling wave solutions of the (3+1) dimensional Boiti–Leon–Manna–Pempinelli (BLMP) equation are obtained using the modified exponential function method. When the solution functions obtained are examined, it is seen that functions with periodic functions are obtained. Two and three dimensional graphs of the travelling wave solutions of the BLMP equation are drawn by selecting the appropriate parameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The matrix reflects the user's rating of the item. The recommendation relation is shown in formula (10).…”
Section: Contextual Interest Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix reflects the user's rating of the item. The recommendation relation is shown in formula (10).…”
Section: Contextual Interest Modelingmentioning
confidence: 99%
“…The experimental evaluation criteria in this paper mainly include two aspects: First, we test whether the parallel mining of big data based on Hadoop can improve the performance of the model calculation. The second is to test situational recommendation mitigation to reduce recommendation accuracy caused by data sparsity [10]. The speedup ratio is mainly used to compare the time it takes for a specific algorithm to run in two different environments, singlemachine, and parallel computing.…”
Section: Dataset and Evaluation Criteriamentioning
confidence: 99%
“…Cordero et al have observed the stability analysis of the fourth-order iterative method in [16]. The (3 +1) Dimensional Boiti-Leon-Manna-Pempinelli equation has been deeply studied in [17]. Using time scale calculus, discrete normal vector field approximation has been presented in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Classical Boussinesq equations have been immensely studied in [20]. Traveling wave solutions of nonlinear Klein Gordon equation were observed in [21] and so on [15,17,18,.…”
Section: Introductionmentioning
confidence: 99%
“…There are many robust, stable, and effective methods that have been developed for constructing exact, approximate analytical and numerical solutions for NPDEs. Particularly, the methods have been extensively used to find exact solutions for NPDEs, such as the (G /G, 1/G)-expansion method [1], the modified G /G 2 -expansion method [2], the Jacobi elliptic equation method [3], the sine-Gordon expansion method [4,5], the extended direct algebraic method [6,7], the modified Exp-function method [8,9], and the Kudryashov method [10,11]. However, the focus of this work is to search for exact solutions of certain nonlinear partial integro-differential equations (PIDEs) converted into NPDEs in some ways.…”
Section: Introductionmentioning
confidence: 99%